Cinema, Social Ties, Emigration and Contemporary Identities in Larga distancia and Voces de un trayecto (Palimpsesto, 2017)
This article intends to investigate the ways in which cinema constructs identities, migratory processes and social ties in contemporary Cuba. For this purpose, two films are analyzed: Larga distancia (Esteban Insausti, 2010) and Voces de un trayecto (Alejandra Aguirre, 2009). We will evaluate how, both fiction and documentary films, encourage the formulation of questions unthinkable decades ago, contributing to the construction of a cinematography that considers essential the investigation on the intricacies of the being in motion.
Keywords: Cinema; Identities; Migration; Cuba; Society.